Embriologia, Apomixia e Poliembrionia em Inga laurina (Sw.) Willd (Fabaceae Mimosoideae) - Araújo, Nayara Augusto Vieira de (2015)
The systematics of Leguminosae is a very discussed topic. Some authors admit three subfamilies that can be distinguished mainly by floral morphology, however, the pollen and embryological data may be important to define the systematic position of a plant group, especially non-clearly monophyletic ones as the Ingeae tribe. Amongst Ingeae, the genus Inga species are characterized by having small flowers with numerous stamens that attract pollinators. Although these floral characteristics influence pollen flow in pollination, many species have self-incompatibility systems to prevent or reduce the self-fertilization and subsequent formation of fruits with viable seeds, among these, some of Inga genus. Inga laurina is a common tree in the Cerrado, which bears legume fruits with polyembryonic seeds. In many species of the Cerrado, polyembryony is associated with polyploidy events and also to apomixis, the asexual reproduction by seed, which influencing the biology of the species. In addition to several embryos, these seeds can produce phenolic compounds that protect them from pathogens. The objectives of this study were to describe the anther and ovule ontogeny of I. laurina, check the breeding system of this species, describe the embryos origin and development, and quantify the presence of phenolic compounds in the seeds. The study was carried out at an urban area in Uberlândia, Minas Gerais, Brazil. Floral buds, flowers and fruits at initial development stages were collected and fixed for anatomical analysis, and the later also used for chemical analysis. In I. laurina the microsporangium wall formation (endothecium, middle layer and tapetum) falls within the development of Dicotyledonous type. Four pollen mother cells were formed that remained together to form a polyad with 16 grains. The ovules are anatropus, bitegmic and the gametophyte develops into a Polygonum type embryo sac. Despite the apparently normal early embryology, the data show that I. laurina is a pseudogamic and apomictic species. The adventitious embryos are nucellar and seem to develop more quickly and can suppress the zygotic embryo due to competition for nutrients. Molecular analyses seem to confirm this characteristic, although also indicated that sexual embryos may also develop in the mature seed. The presence and amount of phenolic compounds in embryos and sarcotesta can promote protection against fungi and environmental pathogens, the germination and the seedling establishment. Phenolic compounds seem to be associated with the size of the embryo and not with its origin. The results support a derived position of the Inga genus in Ingeae tribe, especially in relation to pollen characteristics, and this may contribute to the tribe taxonomic studies. The occurrence of apomixis and adventitious embryony can be considered a strategy to improve the reproductive success, establishment and occupation of the environment. Furthermore, the presence of phenolic compounds in seeds promotes their protection and favors the germination process and dispersion.